Strengthening Organizational Commitment Among Vocational School Teachers: The Roles of Personality, Leadership, Culture, and Job Satisfaction - Griet Helena Laihad; Soewarto Hardhienata; Tiarma Ika Yuliana (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to identify strategies for increasing organizational commitment among permanent foundation teachers at Private Vocational Schools of Computer Engineering and Networking (TKJ) in East Jakarta. A quantitative approach was utilized, employing path analysis on a sample of 195 teachers selected from a population of 381. The findings revealed several significant relationships. Personality had a strong and positive direct effect on organizational commitment (β = 0.737, p 0.05), while transformational leadership also had a positive, albeit smaller, impact (β = 0.089). Organizational culture contributed meaningfully (β = 0.263), and job satisfaction showed a moderate influence on commitment (β = 0.193). Furthermore, personality was positively related to job satisfaction (β = 0.287), as were transformational leadership (β = 0.142) and organizational culture (β = 0.508). Mediation analysis indicated that job satisfaction effectively mediated the relationship between personality and organizational commitment (Z = 3.44 1.96; β = 0.144). However, it did not mediate the relationship between transformational leadership and commitment (Z = 0.991 1.96; β = 0.017). For organizational culture, the mediation effect of job satisfaction was marginal (Z = 1.957 1.96; β = 0.039). These results suggest that enhancing teacher personality traits, fostering a supportive organizational culture, and improving job satisfaction are key strategies to strengthen organizational commitment in TKJ vocational schools.